2014
DOI: 10.1002/arch.21148
|View full text |Cite
|
Sign up to set email alerts
|

BIOTYPE EXPRESSION AND INSECTICIDE RESPONSE OF Bemisia tabaci CHEMOSENSORY PROTEIN‐1

Abstract: Chemosensory proteins (CSPs) are a group of small soluble proteins found so far exclusively in arthropod species. These proteins act in chemical communication and perception. In this study, a gene encoding the Type 1 CSP (BtabCSP1) from the agricultural pest Bemisia tabaci (whitefly) was analyzed to understand sequence variation and expression specificity in different biotypes. Sequence analysis of BtabCSP1 showed significant differences between the two genetically characterized biotypes, B and Q. The B-biotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 45 publications
4
74
0
Order By: Relevance
“…Other representative examples of CSPs performing roles unrelated to chemical communication are the CSP5 of the honeybee, only found in ovaries and eggs and required for development of the embryo (Maleszka et al, 2007), and the CSP4 of Helicoverpa armigera and H. assulta , present in high concentration in the lumen of the proboscis and likely acting as a surfactant to help sucking (Liu et al, 2014a). Recently, CSPs have been also indicated as possible scavengers for insecticides, thus providing insects with a sort of resistance to their lethal effects (Liu et al, 2014b; Xuan et al, 2014). Some OBPs have also been related to roles other than chemoreception: OBP56a is expressed in the oral disk of the house fly Phormia regina and has been reported as a fatty acid solubilizer (Ishida et al, 2013).…”
Section: Soluble Binding Proteins In Detection and Delivery Of Semiocmentioning
confidence: 99%
See 1 more Smart Citation
“…Other representative examples of CSPs performing roles unrelated to chemical communication are the CSP5 of the honeybee, only found in ovaries and eggs and required for development of the embryo (Maleszka et al, 2007), and the CSP4 of Helicoverpa armigera and H. assulta , present in high concentration in the lumen of the proboscis and likely acting as a surfactant to help sucking (Liu et al, 2014a). Recently, CSPs have been also indicated as possible scavengers for insecticides, thus providing insects with a sort of resistance to their lethal effects (Liu et al, 2014b; Xuan et al, 2014). Some OBPs have also been related to roles other than chemoreception: OBP56a is expressed in the oral disk of the house fly Phormia regina and has been reported as a fatty acid solubilizer (Ishida et al, 2013).…”
Section: Soluble Binding Proteins In Detection and Delivery Of Semiocmentioning
confidence: 99%
“…At least in one case, X-ray crystallography has demonstrated that a CSP can swell to a large extent and bind three molecules of 12-Br-dodecanol (Campanacci et al, 2003). The same adaptability is probably the structural reason why CSPs have been adopted in more than one species as scavengers for insecticides of largely different sizes, such as avermectin (Xuan et al, 2014) and thiametoxam (Liu et al, 2014b). …”
Section: Obps and Csps Across Evolution Of Insects And Arthropodsmentioning
confidence: 99%
“…In fact, these proteins have been shown to be involved in development 16-17, immune protection 18-19 and dietary function 20. Interestingly, the first member of the CSP family, before such proteins were discovered in insect antennae, was reported as a regenerating factor in the legs of cockroaches 16.…”
Section: Introductionmentioning
confidence: 99%
“…Another CSP is required for a correct development of the embryo in the honey bee 1-7, while OBPs with unknown functions have been reported in the egg shell of the mosquito Aedes aegypti 21. Some CSPs might also act in a sort of immune protection against insecticides, as their genes have been reported to be upregulated in the gut of some insect species by such chemicals 18-19. Another role, beneficial to the diet, has been reported for an OBP of the house fly Phormia regina .…”
Section: Introductionmentioning
confidence: 99%
“…The finding was made in the insect chemosensory protein (CSP) family, which has been described as being involved in multiple functional systems such as fatty acid transportation, odor recognition, pheromone biosynthesis, insect development, intrinsic tissue regeneration and more recently insecticide resistance in close cooperation with degradative enzymes such as cytochrome P450 oxidases [8][9][10] . Subtle base replacements are found to occur in the RNA sequence to produce proteins with key amino acid substitution, deleted motifs or prominent C-terminal tail in the group of CSPs from the silkworm moth B. mori (BmorCSPs) [6] .…”
mentioning
confidence: 99%